Thematic mapper vegetation indices for determining soybean and corn growth parameters - Thenkabail, Prasad S.; Ward, A.D.; Lyon, J.; Merry, C.J. (1994)
The use of thematic mapper data to study crop growth parameters has primarily been conducted with hand-held and truck-mounted radiometers. In addition, most studies have not used mid-infrared bands to develop vegetation indices. This study used Landsat thematic mapper data and crop parameter data from corn and soybean fields in northern Ohio (1) to develop plant-water sensitive vegetation indices that included the mid-infrared, near-infrared, and red bands; and (2) to compare the ability of different vegetation indices to estimate crop yield, leaf area index, wet biomass, dry biomass, and plant height. Indices which included the mid-infrared thematic mapper bands 5 and 7 performed equal to or better than the widely used near-infrared band 4 and red band 3. The best relationships between vegetation indices and crop parameters had Spearman non-parametric correlation coefficients of 0.80 to 0.89 for all parameters except crop yield which was not highly correlated with the vegetation indices.